Opis poganskega obreda v spodmolu TriglavcaDescription of the Pagan Ritual in the Triglavca Rock Shelter near Divača Village - Čok, Boris (Studia mythologica Slavica, 2010)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The paper describes a Slav pagan ritual of fertility, which took place in the rock shelter of Triglavca near Divača (Slovenia). It was being performed by individual families from the village of Prelože pri Lokvi until the end of the 1830s. The essential element of the ceremony was the ritual entreaty of either the mythological being deva or the divinity Deva to protect the crop on the fields in the forthcoming year from the evil female demon of mora.